Deterjensi Dari Sagu dan Asam Alginat Terdikarboksilasi yang Biodegradabel - Isananto Winursito (Jurnal Riset Teknologi Industri, 2016)
Sago and alginic acid were partially-dicarboxylated and used as an alternative for substitution of sodium tripolyphosphate (STPP) which cause eutrophication in water body. Dicarboxylated sago and alginic acid (ST and AT) with degree of dicarboxylations from 10 to 81 mol% were prepared, and their builder performance in detergent formulation (as relative detergency and calcium ion sequestration capacity), and biodegradabbility were measured. The detergency and calcium ion sequestration capacity of ST and AT depended on the degree of dicarboxylation. AT with degree of dicarboxylations more than 58-60 mol% showed excellent builder performance in detergent formulations based on the detergency and calcium ion sequestration capacity. On the other hand, ST with degree of dicarboxylations more than 25 mol% showed better in biodegradability than AT at the same basis. However, AT with degree of dicarboxylations more than 50 mol% was resistent to biodegradation